EFEKTIVITAS PENGGUNAAN MODEL PROBLEM BASED LEARNING PADA MATERISTATISTIKA UNTUK SISWA KELAS VIII - Setiawan, Deden; Karim, Abdul; Novianti, Idha (Prosiding Temu Ilmiah Nasional Guru, 2023)
The aim of this study is to know the effectiveness of learning mathematics with the PBL model in Class VIII on statistical material. Two classes participated in this study, experimentalclasses with PBL models and control classes with conventional learning models, sampling techniques, data analysis. The results of the research showed that by using the PBL model can improve the student's mathematics learning performance, the Mathematics value of students who study withthe PBL model also more positive results in terms of increased student knowledge value towards mathematical learning compared to students who learn with the conventional model. Thus the effective use of the PBL model can improve student learning performance and studentinterest in learning mathematics. The PBL model can also be an innovative and attractive choice for math teachers. However, additional efforts are needed in developing and adapting the PBL model in order to be effectively applied in different learning contexts.